Elevação e protração do ombro para progressão do cateter central de inserção periférica em recém-nascidos: ensaio clínico randomizado - Nobre, Keline Soraya Santana (2021)
Progression of Peripherally Inserted Central Catheter (PICC) in hemiclavicular region is essential for insertion to the cavoatrial junction. To favor such progression, a Shoulder Elevation, Protraction, and Depression maneuver (EPA Maneuver) was created. This study aimed to evaluate the result of applying the first (elevation) and second (protraction) steps of the EPA Maneuver in the progression of PICC in newborns. It was a randomized clinical trial in two groups, control and intervention, two modalities of independent variable, which were submitted to random allocation, conducted at the neonatal unit in a public maternity hospital in Fortaleza/Ceará, Brazil, from December 2019 to October 2020, with data collected by the researcher and three clinical nurses, registered in a specific instrument. The sample consisted of 77 catheters inserted in 68 newborns, distributed in the control (elevation protraction) and intervention (protraction-elevation) groups. The independent variable was the catheter insertion through the right/left basilic and cephalic veins in newborns, punctured in the forearm, considering inclusion criteria. Data analysis occurred in the Statistical Package for the Social Sciences (SPSS) and applying Pearson’s Chi-square, Fisher’s Exact, Kruskal-Wallis, and Mann Whitney tests. To measure the Effect Size (ES), Eta-squared, Cramer’s V, Point-Biserial correlation, 95% confidence interval, and p-value<0.05 were applied. Normality analysis was performed with Komolgorov Smirnov test. Research ethics committee of the institution approved the study under protocol number 3,545,129. It was registered in the Brazilian Clinical Trials Registry (ReBEC), number RBR-6ng4my. Most newborns were preterm (64-94.1%); corrected age and chronological age <30 days (73-94.8%); birth weight and weight on the day of insertion <1,500g, (46-67.6%) and (50-64.9%), respectively; diagnosis of prematurity and respiratory distress (74-96.1%). There were 243 catheter insertions, of which 166 progressed without maneuvers and 77 with maneuvers. The latter were allocated to the control and intervention groups, 41 and 36, respectively. Of the 166 catheter insertions, 95 (84.8%) progressed without maneuvers in the right basilic vein and 29 (82.9%) in the left, p<0.001 and ES=0.43. In the control group, higher gestational age was related to lower prevalence of progression (p=0.763); in progression after elevation, there was a prevalence of newborns with higher weight (p=0.814); and prevalence of progression on the left; right cephalic vein (9-60%) was the most progressive. The intervention group was more associated with non-progression (27-75%), p=0.025 and ES=0.318; in protraction, higher gestational age was associated with greater prevalence of progression (p=0.053); in progression after elevation, there was a prevalence of newborns with higher weight at birth and on the day of insertion; the right (5-83.3%) and left (2-100.0%) basilic veins were more related to non-progression. In the control and intervention groups, catheterization through the right and left basilic veins obtained central position in 9 (100%) insertions. It is concluded that shoulder elevation and protraction, applied in this order, facilitate the progression of the PICC through the right and left basilic and cephalic veins; it is suggested to maintain the sequence of the elevation-protraction maneuver. This investigation shows the professionals involved in the context of using the PICC that shoulder elevation and protraction, as health technology, favors the advancement of the catheter in newborns, provides humanized care without iatrogenesis, as it is harmless, and without additional costs, thus impacting the quality of care to promote patient health and safety in a complex hospital environment.